Pembelajaran Berdiferensiasi dalam Model Problem Based Learning Terintegrasi Role Play untuk Melatihkan Berpikir Kritis Peserta Didik - Much. Solikhin; Akbar Aji Seno; Budhi Utami (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2023)
Students' critical thinking skills are still in the low category. Students are familiar with questions at the Low Order Thinking Skills (LOTS), which rely on memory and memorization, so when faced with problems that require critical thinking to analyze and solve problems, they tend to have difficulty. This study aims to improve students' critical thinking through integrated role play problem based learning. This study used the class action research method, which was carried out in three cycles. The research subjects were 35 students in class VII C of SMP Bina Insan Mandiri. The instrument used in this study is a test item according to critical thinking indicators. The data analysis technique used in this study is a qualitative descriptive technique. The results of method showed the average student's critical thinking increased from the pre-cycle to the last cycle. During the pre-cycle, the average critical thinking of students was 35% in the low category; cycle 1 was 55% in the medium category; cycle 2 was 70% in the high category; and cycle 3 was 81% in the very high category. It can be concluded that differentiated in problem-based learning integrated with role play can improve students' critical thinking in science learning.